ANALISIS KEBANGKRUTAN PERUSAHAAN DENGAN METODE ALTMAN PADA PERUSAHAAN ROKOK YANG LISTING DI BEI PADA TAHUN 2012-2016 - Putri Yudiastantri; Nur Hidayati; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research was conducted to analyze the potential losses to Cigarettecompanies listed on Indonesia Stock Exchange period 2012-2016 using Altman (Z- Score) that model is by giving score against value that will appear based on theformula that has been determined. Based on sampling criteria that have beendone before then got 4 companies that found the criteria and can be used as asample in this study. The list of companies to be used as sample in this research isPT Gudang Garam Tbk, PTWismilak Inti Makmur Tbk, PT Bentoel InternasionalInvestama Tbk, PT HM Sampoerna Tbk. Based on the test results using Z-ScoreAltman got the results, like:Most of the sample companies in the study were in sound financial condition anddid not go bankrupt. In the year 2014 on the results of the test bankruptcy Altmanshowed that PT Gudang Garam Tbk experiencing a risky situation is evidenced bycorporate debts that always increased from 2013 to 2014 from21,353,980,000,000 to 24,991,880,000,000 which became one of the reasons whyin 2014 PT Gudang Garam Tbk entered in the vulnerable zone.PT Bentoel Internasional Investama Tbk which is believed to have bankruptcy in2013 and 2015 is indicated by Z Score value of less than 1.81 and proved by theresult of financial statement showing that in 2015 PT Bentoel InternationalInvestama Tbk suffered losses. Then in 2016 there was a difference of resultsstating that PT Bentoel International Investama Tbk experienced an increase fromthe company that declared bankruptcy to be a risky company.The company of PT Wismilak Inti Makmur Tbk in the Z-Score analysis is in avulnerable condition in 2012 because of the decline in corporate earnings and theincreasing value of the debt that makes the company in a vulnerable condition,this is indicated by the Z-Score value of less than 2.99 in that year.Keyword : Bankruptcy, Z-Score Altm